On The Validity of Minimum Magnetizability Principle in Chemical Reactions - Hiteshi Tandon; Tanmoy Chakraborty; Vandana Suhag (Acta Chimica Slovenica, 2021)
A new principle known as Minimum Magnetizability Principle has recently been introduced in the context of Density Functional Theory. In order to validate this principle, changes in the magnetizability (Δξ) and its cube-root (Δξ1/3) are computed at B3LYP/LanL2DZ level of theory for some elementary chemical reactions. The principle is found to be valid for 77% of reactions under study. It is observed that the molecules with the lowest sum of ξ or ξ1/3 are generally the most stable. The principle fails to work in the presence of hard species. A comparative study is also made with change in hardness (Δη), electrophilicity index (Δω), polarizability (Δα) and their cube-roots (Δη1/3, Δω1/3, Δα1/3). It is observed that the Minimum Magnetizability Principle is nearly as reliable as Minimum Electrophilicity Principle. It appears that this principle could be helpful in predicting the direction of diverse reactions as well as stable geometrical arrangements.